Upaya Guru Tahfidz dalam Meningkatkan Hafalan Al-Qur’an Siswa Di SDIT Ustman Bin Affan Surabaya - Muhammad Luthfi Efendi; Zakiyudin Fahmy; Ria Resti Fauziah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
Memorizing the Qur'an is not something easy but it is also not impossible, because at the time of the Prophet many people memorized the Qur'an. In public or private schools, introducing students to the Koran, teaching them to read and memorizing it is the responsibility of a teacher. Therefore, to be able to fulfill his duties as a teacher in providing guidance, the teacher must of course make various efforts because the success or success of a student in memorizing depends on the efforts made by the teacher. The aim of this research is to determine the efforts of a tahfidz teacher and the obstacles – what obstacles do teachers face in improving students' memorization of the Koran at SDIT Ustman Bin Affan Surabaya. This research is qualitative field research. The subjects of this research were tahfidz teachers, as well as students at SDIT Ustman Bin Affan Surabaya. The data collection method uses observation, interviews and documentation. After that, the data is presented in an appropriate form so that it is easy to read and can be understood, then the data is analyzed and conclusions are drawn. Based on the research results, the efforts made by teachers to improve students' memorization of the Qur'an at SDIT Ustman Bin Affan Surabaya are: providing motivation to students, giving assignments and punishments to students, guiding students to remain muraja'ah, using appropriate methods. varies. Apart from teachers trying to improve students' memorization of the Qur'an, tahfidz teachers also experience obstacles, including: there are students who still do not read the Qur'an well, teachers' health which can interfere with teaching and learning activities, lack of motivation from students in memorizing the Qur'an, there is a feeling of laziness on the part of students when memorizing the Qur'an, as well as time allocation